The impact of EAP study on the academic experiences of international postgraduate students in Australia - Abdul Wahid, Mohd Ridwan; Terraschke, A. (Elsevier BV, 2011)
EAP courses usually not only aim to improve students’ level of English but also to convey useful academic study skills and introduce students to the common genres of their discipline. These are extra skills and information other international students do not have ready access to. Yet, few studies have focused on how the academic experiences of international students are affected by whether they had attended an EAP course or not.The present study aims to shed some light on this issue by comparing accounts of students who completed a pre-sessional EAP course with those of students who gained direct entry to their degree. A qualitative analysis of a series of semi-structured quarterly interviews suggests that both groups of students had similar experiences in terms of listening, speaking and reading for their degree course. However, former EAP students were better able to talk about their use of learning strategies, appeared to be more conﬁdent in dealing with written assessments and were found to have a better understanding of the demands of their course. Students who did not attend an EAP course, on the other hand, expressed a greater sense of dissatisfaction and disappointment when their high academic expectations were not fulﬁlled.